Further Training and Affective Commitment - Christian Grund; Krystina Titz (Institute of Labor Economics (IZA), 2018)
We investigate the relation of further training and employees' affective commitment. In doing so, we distinguish between a support effect and a participation effect: On the one hand we analyze how a firm's general support for further training is associated with the affective commitment of their employees and on the other hand how individual participation in further training relates to affective commitment. Using the Linked Personnel Panel (LPP), which is a longitudinally linked employer-employee data set, we are able to control for several human resource management instruments additionally to the usual demographics and job characteristics. Moreover, the two-level structure of the data allows us to analyze the support effect from a firm's perspective and an individually perceived perspective. Results show that employees' participation in further training is positively related to affective commitment, but that a general perceived firm's support for personnel development mediates the positive relation of participation in further training and individual affective commitment. Furthermore, we find that the relation of perceived firm's interest in personnel development and affective commitment is increasing with years of schooling and decreasing with age.
Keywords: M53; M12; J24; 330; commitment; further training; signalling; linked employer-employee data